Recreational Female Runners Report Diverse Pelvic Health Symptoms Beyond Urinary Incontinence: Sport-Specific Screening Matters - Julie W. Wiebe; Jennifer LaCross; Laurel Proulx; Christopher Napier (Journal of Athletic Training, 2026)
ABSTRACT Context: Many female athletes experience a range of pelvic floor dysfunction-related symptoms with negative effects on performance, quality of life, and mental health. Investigations have primarily focused on stress urinary incontinence, creating critical knowledge gaps regarding how diverse symptoms impact athleticism and individualized sport-specific programming. Objective: Identify the prevalence of a range of pelvic floor dysfunction-related symptoms in a group of recreational female runners and compare their responses on a validated measure with symptoms experienced during running. Design: Cross-Sectional Setting: Online surveys Participants: Following a biomechanical treadmill study, 88 recreational female runners were invited to complete pelvic health surveys. Sixty-six participants met additional inclusion criteria and completed surveys. Main Outcome Measure(s): The Australian Pelvic Floor Questionnaire identified symptoms of pelvic floor dysfunction, the Epidemiology of Incontinence and Prolapse Questionnaire captured obstetrical variables, and bespoke questions collected running related symptoms. Descriptive statistics summarized participant characteristics and survey responses. Prevalence data obtained from questionnaires and running-related responses were analyzed. McNemars Test compared paired symptom prevalence that differed between instruments. Results: Dyspareunia (painful intercourse) was the most frequently reported symptom (44.6%). Comparison of symptom prevalence reported on the Australian Pelvic Floor Questionnaire versus during running yielded: stress urinary incontinence (36.4% vs. 18.2%, p = 0.014), pelvic organ prolapse (9.2% vs. 4.6%, exact p = 0.375), and fecal incontinence (12.3% vs 10.6%, p = 1.000). Conclusions: Recreational female runners experienced a broad range of pelvic floor dysfunction-related symptoms. Approximately two-thirds of participants who reported stress urinary incontinence and pelvic organ prolapse symptoms on a general pelvic health questionnaire did not report these symptoms during running. Athletic trainers and clinicians should screen for pelvic floor dysfunction beyond stress urinary incontinence and ask sport-specific questions if symptoms are identified to guide treatment planning and optimize referral pathways.